Model Transportasi dalam Meminimumkan Biaya Distribusi Beras Kemasan - Adoe, V S (Program Studi Matematika, Universitas Tadulako, 2021)
Rice is a strategic commodity that a very important role as the main staple food for the majority of people in Indonesia. Rice has its own distribution development pattern that provides added value to business actors.